ENGLISH NOUNS AND VERBS MORPHOLOGICAL INFLECTION MISTAKES AMONG UNIBA’S TOEFL PREPARATION STUDENTS’ ASSIGNMENTS - Adhitya Darmawan (Universitas Wiralodra, 2024)
This research attempts to find and describe the types and factors of English nouns and verbs morphological inflection from the student's assignments. This research can also be seen as one form of language development research since it also discusses the factors of the mistakes that the students commit in the making of the assignment. The assignment was to write a paragraph about anything in English then the outcome was analyzed to find the morphological inflection mistakes and classify the data based on the criteria. This research applies descriptive qualitative design and uses observation for the data collecting technique and later uses document analysis. The techniques in this research are Spradley's domain, taxonomy, and componential analysis. This research finds 16 data of inflectional mistakes that fulfill the three categories of the factors while the discussion shows that the factor following each type is dominated by unfamiliarity with inflectional rules whereas the dominant type of inflectional mistake is omission. The conclusion shows that the most common mistakes happen in nouns by the supports from Tomasello's Usage-based theory (2009). Finally, the students mostly fail on noun inflection because they are unfamiliar with the inflectional rules of nouns.